Students as Engaged Partners in Directed Research Courses - Benenson, Jodi; Johnson, Skylar (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
This report from the field reflects on the authors’ experiences in a directed research course on the topic of youth civic engagement in Canada. A literature review was co-written as part of a directed research course where the instructor was a visiting professor from the United States and the student was an undergraduate student in Canada. The content of this report was gathered during various stages of the directed research course and is informed by literature focused on students as engaged partners in teaching and learning in higher education. Specifically, we reflect on the ways viewing students as engaged partners can leverage their knowledge and lived experiences when engaging in directed research courses, especially when the student and faculty member may be coming from different countries in North America. In addition, we reflect on how designing a directed research course that views students as engaged partners can provide a rich ground for the redistribution of power in higher education and strengthen the quality of research through the co-creation of new knowledge and ideas.